Directional Coherent Wave Group From an Assimilated Non-linear Wavefield - Waseda, Takuji; Watanabe, Shogo; Fujimoto, Wataru; Nose, Takehiko; Kodaira, Tsubasa; Chabchoub, Amin (Frontiers in Physics, 2021)
The presence of coherent wave groups in the ocean has been so far postulated but still lacks evidence other than the indication from the radar images. Here, we attempt to reconstruct a wave field to monitor the evolution of a directional wave group based on a phase resolving two-dimensional nonlinear wave model constrained by the stereo images of the ocean surface. The reconstructed wave field of around 20 wavelength squared revealed a coherent wave group compact in both propagating and transverse directions. The envelope of the wave group seems to be oriented obliquely to the propagation direction, somewhat resembling the directional soliton that was theoretically predicted and experimentally and numerically reproduced recently. A comparison with a constrained linear wave model demonstrated the coherence of the nonlinear wave group that propagates for tens of wavelengths. The study elaborates a possibility of a spatially coherent short crested wave group in the directional sea.